THE USE OF MICROSOFT TEAMS IN LEARNING ENGLISH FOR SECONDARY LEVEL: TEACHERS’ AND STUDENTS’ VIEWS - Dewi, Dian Novita; Amalia, Nurul; Degeng, Putu Dian Danayanti (Erudio Journal of Educational Innovation, 2022)
Education in Indonesia has undergone a change from face-to-face learning in class to online learning due to the spread of the coronavirus (COVID-19). To support the online learning practices, SMP Brawijaya Smart School utilizes Microsoft Teams as the platform especially for online English learning. This study aims to find out teachers’ and students’ perception in using Microsoft Teams in learning English. The sample of this study was 2 English teachers’ and 180 students from 8th and 9th grades. To reach the aim of the study, quantitative research with survey design was used, with questionnaire to collect the data was conducted, and with SPSS to analyze the quantitative data was used. The results showed that teachers and students at SMP Brawijaya Smarts School had a positive perception of using Microsoft Teams in learning English. Teachers’ and students also found out that learning English through Microsoft Teams was easy to be used because Microsoft Teams provided many features that the teachers and students can access in one platform. In another say, Microsoft Teams is the one-stop platform for learning.